The Intercultural Identities of Nonnative English Teachers: An Overview of Research Worldwide (Asian Education Studies, 2016)
Nonnative-English-speaking teachers who teach English as a second or foreign language (ESL/EFL) can play an important role in the promotion of intercultural competence and often have an advantage over native-English-speaking ESL/EFL teachers because they once were language learners and more aware of the difficulties that students can encounter. Therefore, a better understanding is needed of nonnative ESL/EFL teachers in language-and-culture teaching contexts. Research on how these teachers view themselves in relation to two or more cultural groups, i.e., teachers’ intercultural identities is useful in this respect, but has been scarce. In the present study, we systematically reviewed 21 studies on the intercultural identities of nonnative ESL/EFL teachers. Our study provides insight in key characteristics of these teachers’ intercultural identities, factors in the formation of these teachers’ intercultural identities, inconsistencies in studies to date, and directions for further research.